Consumption as a Factor of Polish Economic Growth During the Global Recession of 2008/2009: A Comparison with Spain and Hungary - Tomasz Jasiński; Paweł Mielcarz (Contemporary Economics)
The economic recession of 2007-2009 proved to be a difficult period for most European economies. Poland was among the few countries that recorded positive gross domestic product (GDP) growth during that period. The main reason for its performance was that private consumption stimulated the GDP. The goal of this study was to explore the reasons that private consumption in Poland did not collapse during the economic recession through the substantial economic literature on this topic. The study compared Spain, Hungary and Poland from 2007 to 2009 to find differences specific to the latter. The most important factors differentiating Poland identified in this study were the confidence of Polish consumers in the economy and a high propensity to spend resulting in lower savings. Additional factors were a relatively low unemployment rate and relatively easy access to credit.